THE BASIC IDEAS OF WESTERN CIVILIZATION AND ITS EFFECTS ON MUSLIM RELIGIOUS AND POLITICAL THOUGHT: مغربی تہذیب کے بنیادی نظریات اور مسلم دینی و سیاسی فکر پر اس کے اثرات (عصر حاضرکے تناظر میں) - `, Muhammad Ikram ul Haq; Dr. Nasir Ali Khan (International Research Journal of Arabic and Islamic Studies, 2021)
Western civilization has dominated the whole world and Muslim society seem to be influenced by it .This article discusses these basic ideas of western civilization that it made the man completely independent and religion was expelled from the collective life of man and all supernatural things were denied .From the point of view humanism lord was clearly denied and it was said the man is not a salve to any one ,if anyone is worthy of worship it is man himself .Although humanism completely removed religion from human life ,the sanctity of religion remained in the minds of the people for this the ideology of the secularism was introduced in which man was allowed to include religion in his individual life .Muslims have become so influenced by western civilization that they have forgotten these basic ideas .By following them Muslims are rulers of world up to a thousand years .This article described in detail the political of views of Muslims especially the significant changes that have taken place in the system of government.